503 Implementing a formal research mentoring training program at the Miami Clinical and Translational Science Institute: early findings and outcomes. (April 2022) - Avissar, Patricia; Alcaide, Maria; Fornoni, Alessia; Levy, Robert; Das, Rosalina
Abstract : OBJECTIVES/GOALS: The goal of this study is to describe the implementation of a formal research mentoring training program at Miami CTSI in collaboration with University of Colorado CTSI, to build effective mentor-mentee relationships that help build successful research careers for junior faculty. METHODS/STUDY POPULATION: The Miami CTSI Research Mentoring Training is a three-part series for early stage faculty and their mentors to strengthen mentoring skills and build successful relationships. The curriculum uses evidence-based strategies and is modeled after University of Colorado CTSIs CO-Mentor Training Program. The pilot training was conducted as a train-the-trainer program with subsequent workshops led by Miami CTSI faculty. The program has mentee-only, mentor-only, and joint sessions covering topics such as networking skills, managing financial aspects of an academic career, and career mapping. To assess program effectiveness, pre/post surveys were conducted and follow up surveys are planned. Data collected will assess participant diversity, research productivity, and mentoring relationship status. RESULTS/ANTICIPATED RESULTS: A total of 49 mentor-mentee teams from 18 departments participated in the training over two cohorts. An upcoming third cohort will be included in the analysis. Overall, 100% mentors and 86% mentees reported the overall value of the program as positive. Post-training, mentees reported an increase in confidence in creating career development plans and articulating career goals. Mentors reported an increase in confidence in providing guidance tailored to mentees needs. Mentees reported improvement in their knowledge of developing personal narratives and handling financial aspects of research; both mentors and mentees reported improvement in insights into achieving work-life balance. Follow up survey results will provide insight into the evolution of the mentoring relationships. DISCUSSION/SIGNIFICANCE: Miami CTSIs mentoring training demonstrated successful participation and positive feedback from mentors and mentees and is poised to become a critical component of the Miami CTSIs research career development pipeline.